Tire Deformation-Based Regulation of Braking Torque in Manual Wheelchairs Equipped with Reverse Locking Modules - Bartosz Wieczorek; Łukasz Warguła; Marcin Giedrowicz (PLoS ONE, 2025)
Moving in a manual wheelchair involves overcoming various architectural and terrain barriers. One of the obstacles that most burdens the muscular system and generates a high risk of instability is the climb up a slope. This article presents a comprehensive regulation method that allows for achieving the desired braking torque of the locking module based solely on tire deformation measurements, rather than the previously used contact force. To address the research problem, a research method was developed, consisting of three experimental tests and one mathematical analysis. The experiments included the measurement of the sliding force moment (E1), braking torque (E2), and tire deformation (E3). Using these methods, a measurement procedure was formulated to allow the measurement of the braking torque generated by the reverse locking module through tire deformation. Research on braking torque Mh showed that for wheelchairs with 24’’x1’’ wheels and a tire pressure of 4-7 bar, tire deformation eT, depending on the diameter of the pressing roller, ranges from mm to mm. For a constant roller diameter of 70 mm, to achieve a torque of 7.5 Nm, the deformation was mm, and for 12 Nm – mm. The sliding force FZ increased by 57% with the user’s mass rising from 50 kg to 90 kg (from N to N at a pressure of 7 bar). ANOVA analysis confirmed that both the nominal contact force FdN and the diameter of the roller dr had a significant impact on the braking torque Mh. Verification of the developed mathematical model of braking torque as a function of tire deformation showed an error range of 3% to 7%.